Preventing Electrolyte Decomposition on a Ca Metal Electrode Interface Using an Artificial Solid‐Electrolyte Interphase. Issue 8 (9th July 2021) - Young, Joshua; Smeu, Manuel
Abstract: Calcium ion batteries are gaining attention as alternatives to lithium‐ion technology because they offer comparable properties at reduced cost and improved safety. However, progress has been limited because of the inability to efficiently and reversibly plate and strip Ca metal anodes in organic electrolytes. Moreover, the inorganic components of the solid‐electrolyte interphase (SEI) that form via decomposition of the electrolyte often do not allow for the diffusion of Ca ions. In this work, an approach combining density functional theory and ab initio molecular dynamics (AIMD) simulations is utilized to show that the use of a preformed artificial SEI layer of amorphous Al 2 O 3 can potentially prevent electrolyte decomposition. First, Ca is shown to be able to intercalate into an amorphous Al 2 O 3 layer (up to Ca1.5 Al2 O3 ) and diffuse through on a reasonable time scale. Through calculation of the density of states, the system is found to remain insulating up to the equilibrium stoichiometry. Finally, AIMD simulations with a realistic organic electrolyte environment are used to show that this calcinated Al 2 O 3 layer completely prevents the decomposition of solvent molecules. This approach can provide a route to efficient rechargeable Ca ion batteries, paving the way for cheap large‐scale energy storage. Abstract : The development of rechargeable calcium ion batteries using organic electrolytes has been hampered because of the decomposition of the solvent on the anode creating an impermeable barrier. Here, computational methods demonstrate that an amorphous Al 2 O 3 layer can prevent this decomposition and provide a new route to such batteries.